OsCBL1 mediates rice response to local nitrate signaling: insights into regulatory networks and gene expression - Hu, Zhao; He, Dongchen; Peng, Xiaojue; Yang, Jing (Frontiers in Plant Science, 2024)
Nitrate is a significant source of nitrogen in soils and also serves as a critical signal for root development. Previous studies have demonstrated that the local nitrate supply promotes lateral root elongation primarily through local nitrate signals, rather than nutritional effects. In this study, we report that Calcineurin B-like protein 1 (OsCBL1) positively regulates local nitrate signaling, thereby triggering lateral root colonization, as revealed by a comparative analysis of the phenotype and whole transcriptome of the knockdown mutant (OsCBL1-KD) and the wild-type (WT). In the split-root system, the knockdown of OsCBL1 was found to inhibit local nitrate-induced lateral root growth. Transcriptome analyses identified 398 differentially expressed genes (DEGs) that were under the control of OsCBL1 and associated with the phenotype of nitrate-induced lateral root colonization. Further analysis revealed that the nitrate transporter/sensor gene OsNRT1.1B was up-regulated under Sp-NaNO3 conditions compared to Sp-NaCl in WT but not in OsCBL1-KD plants. Pathway mapping of DEGs (i.e., genes exhibiting a significant change in expression in the Sp-NaNO3 condition compared to the Sp-NaCl condition) revealed a preferential upregulation of genes involved in lignin biosynthesis and a downregulation of genes involved in auxin and salicylic acid signaling. This suggests that OsCBL1 might function as a transmitter within the auxin, salicylic acid signaling, lignin biosynthesis, and nitrate sensor (OsNRT1.1B)-mediated pathways in response to local nitrate signaling. We also identified a transcriptional regulatory network downstream of OsCBL1 in nitrate-rich patches that is centered on several core transcription factors. Our study provides new insights into how plants adapt to an inhomogeneous distribution of nitrogen in the soil.